Evangelising 19th-century Italy?: Translation and the transnational migration of cheap Evangelical tracts. (3rd April 2019) - Colombo, Alice
ABSTRACT: Translation scholars have so far studied religious texts largely in relation to the transnationalisation of canonical texts in the codex and printed book format. Religious publishing, however, extends to other, more ephemeral publications. The focus of this article is on Protestant tracts, which proliferated throughout the nineteenth century in connection with the Evangelical Revival. Translation of tracts was crucial to the crusade led by the Evangelicals to disseminate their doctrine. The article first gives insights into the translational and transnational extent of this crusade. Then it examines the cultural and social impact of translated tracts in the Italian Catholic context with particular reference to a corpus of children's publications. The article also provides a bibliographical and historiographical analysis which shows that the impact of translated Protestant tracts in Italy was not, as has previously been argued, a post-1848 phenomenon.